Apoptosis triggered by isoquercitrin in bladder cancer cells by activating the AMPK-activated protein kinase pathway. Issue 10 (26th September 2017) - Wu, Ping; Liu, Siyuan; Su, Jianyu; Chen, Jianping; Li, Lin; Zhang, Runguang; Chen, Tianfeng
Abstract : Our findings provide comprehensive evidence that isoquercitrin (ISO) influenced T24 bladder cancer cell metabolism by activating the AMPK pathway as identified by combination with metabolomics and immunoblotting assay. Abstract : Cancer cells are well known to require a constant supply of protein, lipid, RNA, and DNA via altered metabolism for accelerated cell proliferation. Targeting metabolic pathways is, therefore, a promising therapeutic strategy for cancers. Isoquercitrin (ISO) is widely distributed in dietary and medicinal plants and displays selective cytotoxicity to cancer cells, primarily by inducing apoptosis and cell cycle arrest. The aims of this study were to find out whether ISO could stabilize in a bladder-like acidic environment and inhibit bladder cancer cell proliferation by affecting their metabolism, and to investigate its molecular mechanism. In this study, the exposure of T24 bladder cancer cells to ISO (20–80 μM) decreased cell viability by causing ROS overproduction. This ROS change regulated the AMPK signaling pathway, and caused Caspase-dependent apoptosis as well as metabolism dysfunction. Metabolic alterations elevated metabolic pathway variation, which in turn destabilized lipid synthesis and altered anaerobic glycolysis. This linkage was proved by immunoblotting assay, and metabolomics as identified by UHPLC-QTOF-MS. Our findings provide comprehensive evidence that ISO influenced T24 bladder cancer cell metabolism, and that this process was mainly involved in activating the AMPK pathway. This study could lead to an understanding of how ISO suppresses bladder cancer cell growth, and whether the affected cancer metabolism is a common mechanism by which nutritional compounds suppress cancers.